Influence of Sulfurization Temperature on Photoelectric Properties Cu2SnS3 Thin Films Deposited by Magnetron Sputtering - Pengyi Zhao; Shuying Cheng (Advances in Materials Science and Engineering)
Cu2SnS3 is a narrow-band-gap semiconductor material. It has suitable optical and electrical properties which make it a potential absorber layer of solar cells. In this paper, Cu2SnS3 thin films were successfully obtained by sulfurizing CuSnS2 thin films deposited by RF magnetron sputtering at temperatures of 350–425°C for 2 h in an atmosphere of hydrogen sulfide and nitrogen. The influence of the sulfurization temperature on the electrical and optical properties of the Cu2SnS3 thin films was investigated. The experimental results show that the Cu2SnS3 thin films sulfurized at a temperature of 425°C exhibit better properties than others. The mobility and resistivity of the Cu2SnS3 films are 9 cm2/V·s and 3 Ω·cm, respectively. And its optical band gap is estimated to be about 1.77 eV.